Proceedings of the 3rd Borobudur International Symposium on Humanities and Social Science 2021 (BIS-HSS 2021) 2023
DOI: 10.2991/978-2-494069-49-7_67
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Attachment to God and Students' Psychological Well-Being

Abstract: This study aims to determine the relationship between attachment to God and psychological well-being among 244 Muslim students. This study is quantitative in nature because it uses a Likert scale. Data were collected using the Short 18 item scale of psychological well-being developed by Ryff and the Muslim Spiritual Attachment Scale (M-SAS) by Yildiz. The hypothesis shows that there is a positive correlation between attachment to God and emotional stability. The results showed that there was a positive relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, contrary to the concept of psychological well-being, based on the results of research by Aulia & Panjaitan [4] found that 47.2% of final-year students had a low level of psychological well-being. Meanwhile, other research by Ningrum et al [17] also stated that 47% of final-year students had low psychological well-being. Final-year students will face greater demands, namely having the obligation to complete the final project or thesis.…”
Section: Introductionmentioning
confidence: 95%
“…However, contrary to the concept of psychological well-being, based on the results of research by Aulia & Panjaitan [4] found that 47.2% of final-year students had a low level of psychological well-being. Meanwhile, other research by Ningrum et al [17] also stated that 47% of final-year students had low psychological well-being. Final-year students will face greater demands, namely having the obligation to complete the final project or thesis.…”
Section: Introductionmentioning
confidence: 95%
“…The scale consists of six sub-dimensions: autonomy, environmental mastery, personal growth, positive relationships with others, purpose in life and selfacceptance. Reverse-coded items in each subscale are as follows: Autonomy: 2,20,32,44,56,62,74;Environmental Dominance: 9,15,27,45,63,75;Personal Growth: 4,22,34,58,76,82;Positive Relationships with Others: 7,13,31,43,55,61,73;Purposes in Life : 11,17,29,35,41,65,24,42,54,60,66,84. 20…”
Section: Psychological Well-being Scalesmentioning
confidence: 99%
“…This study is consistent with some studies in terms of its findings on the relationship between perception of God, attachment to God, emotional state and psychological wellbeing. 31 The anxiety levels of individuals with chronic diseases are higher than other emotional states. This condition can be associated with the disease.…”
Section: Fatma Sağlam Demi̇rkanmentioning
confidence: 99%